Predict-Observe-Explain (POE) Method with the Assistance of Outdoor Learning on Science Process Skills in Science and Social Studies (IPAS) in Sixth Grade Students - Ni Nyoman Triska Novita Dewi; I Gusti Putu Suharta; Dewi Anzelina (International Journal of Language and Literature, 2025)
The low science process skills of students are caused by the dominance of lecture methods and minimal experimental activities, so that learning becomes less meaningful and does not encourage scientific thinking skills. This study aims to analyze the significant influence of the lecture method and the lack of experimental activities, so that learning becomes less meaningful and does not encourage scientific thinking skills.predict, observe, explain (POE) assisted learning outdoorson the science process skills of grade VI elementary school students. This study uses a quantitative research type with a quasi-experimental research type (quasi-experimental design) consisting of three stages: preparation, implementation, and ending. The population in this study were all sixth grade elementary school students consisting of three classes, namely VI A, VI B, and VI C, with a total of 80 students. The sample of this study was selected using the Cluster Random Sampling technique. The data collection method in this study involved two main approaches, namely observation and testing. The data analysis methods used in this study included descriptive and inferential statistics. The results showed that this approach significantly improved the science process skills of sixth grade students in the Natural and Social Sciences (IPAS) subject. Students who took part in learning with the POE method outdoors showed an increase in their ability to observe, ask questions, formulate hypotheses, conduct experiments, and draw conclusions systematically. In conclusion, the application of the POE method assisted by outdoor study had a significant effect on students' science process skills and understanding. The implication is that this method can be applied to improve science skills and understanding in IPAS learning in elementary school.